The Building Stock in the City of Dubai: A Survey Methodology (Future Cities and Environment, 2022)
In 2003, new building regulations were introduced in the city of Dubai. In 2012, the municipality requested a survey of every building that existed prior to that year. This paper documents the method used for this significant undertaking, not performed by any other large city. The survey was conducted using a combination of Global Positioning System (GPS)-enabled photography and field visits. Multiple images were taken of every street, resembling progressive film imagery, with every building recorded multiple times in the image sequence. The location-tagged images were superimposed on a city map and compared to historical satellite maps of the city from Google Earth history timelines. Whenever the photographic data was not enough to adequately classify a building, field visits were conducted. That was necessary for around 10% of the city structures. The fieldwork was conducted by two teams, each comprising two engineers, and took four weeks to complete. The results showed that, in 2003, there were around 37,000 buildings in the city. Of those, almost 89%, were low-rise (1–2 floors) and largely single-unit residential houses. Nearly all buildings were found to be built after the mid-1980s, and in very good structural condition. The system described in this paper may be applied to any other large-scale city building survey.